Research on Optimized Path of Machine Translation from the Perspective of Cognitive Approach - Collaborative Development of Human Translation and Machine Translation - Si, Gou (Transactions on Social Science, Education and Humanities Research, 2024)
This study, starting from the cognitive perspective, delves into the optimized paths for machine translation and focuses on the coordinated development strategies between human translation and machine translation. By analyzing the application of cognitive approach in translation activities, this paper proposes methods such as enhancing the cognitive mechanisms of understanding and expression in machine translation, optimizing algorithms, and improving translation quality using cognitive feedback loops. Additionally, this paper also explores collaborative development strategies including human-machine interaction interface design, collaborative translation process management, translation quality control and evaluation mechanisms, as well as translator training and education based on cognitive approach. These strategies aim to improve the accuracy and efficiency of translation, meet the personalized needs of users, and promote the deep integration and development of human translation and machine translation.